Evaluation and validation of the prognostic value of anti-MDA5 IgG subclasses in dermatomyositis-associated interstitial lung disease. (12th April 2022) - Xu, Yue-Tong; Zhang, Ya-Mei; Yang, Hong-Xia; Ye, Li-Fang; Chen, Fang; Lu, Xin; Wang, Guo-Chun; Peng, Qing-Lin
Abstract: Objective: To investigate the association between the anti-melanoma differentiation associated gene 5 (MDA5) IgG subclasses and prognosis of patients with dermatomyositis (DM)-associated interstitial lung disease (ILD). Methods: This retrospective study included 122 anti-MDA5 positive DM-ILD patients admitted from October 2017 to October 2020 as training cohort, and additional 68 patients from August 2014 to September 2017 as validation cohort. The levels of anti-MDA5 total IgG and IgG subclasses were measured using in-house enzyme-linked immunosorbent assays, and analysed in association with the patient prognosis. Results: In the training cohort, the concentrations of anti-MDA5 IgG1 and IgG3 in non-survivors were significantly higher than in survivors ( P < 0.05), whereas there were no significant differences in the IgG2 and IgG4 levels. Kaplan–Meier survival analysis revealed that the levels of anti-MDA5 total IgG, IgG1 and IgG3 were associated with mortality ( P < 0.05). Multivariate analysis revealed anti-MDA5 IgG1 >13 U/ml and anti-MDA5 IgG3 >11 U/ml were independent risk factors for death of DM-ILD patients ( P < 0.05). Anti-MDA5 IgG1 was confirmed as an independent risk factor in the validation cohort, while anti-MDA5 IgG3 was not. Anti-MDA5 IgG1 showed greater discriminable power for patient prognosis (Youden index 0.494) than anti-MDA5 total IgG, IgG3, or the combination of IgG1 and IgG3 (Youden index 0.356, 0.32 and 0.447, respectively). Conclusion: Anti-MDA5 IgG1 and IgG3 are significantly associated with poor prognosis in DM-ILD patients, and anti-MDA5 IgG1 is more efficient as a prognostic biomarker in DM-ILD patients.